Decision-Making in the Ventral Premotor Cortex Harbinger of Action - Pardo-Vázquez, José L.; Padron, Isabel; Fernandez-Rey, José; Acuña, Carlos (Frontiers in Integrative Neuroscience, 2011)
Although the premotor cortex (PM) was once viewed as the substrate of pure motor functions, soon it was realized that it was involved in higher brain functions. By this it is meant that the PM cortex functions would better be explained as motor set, preparation for limb movement or sensory guidance of movement rather than solely by a fixed link to motor performance. These findings, together with a better knowledge of the PM cortex histology and hodology in human and non-human primates prompted quantitative studies of this area combining behavioral tasks with electrophysiological recordings. In addition, the exploration of the PM cortex neurons with qualitative methods also suggested its participation in higher functions. Behavioral choices frequently depend on temporal cues, which together with knowledge of previous outcomes and expectancies are combined to decide and choose a behavioral action. In decision-making the knowledge about the consequences of decisions, either correct or incorrect, is fundamental because they can be used to adapt future behavior. The neuronal correlates of a decision process have been described in several cortical areas of primates. Among them, there is evidence that the monkey ventral premotor cortex (PMv), an anatomical and physiological well-differentiated area of the PM cortex, supports both perceptual decisions and performance monitoring. Here we review the evidence that the steps in a decision making process are encoded in the firing rate of the PMv neurons. This provides compelling evidence suggesting that the PMv is involved in the use of recent and long-term sensory memory to decide, execute and evaluate the outcomes of the subjects’ choices.